The Uses of Humour in Spanish Environmental Education: An Exploratory Qualitative Analysis of the Potentialities, Limitations and Good Practices of Humour - Jorge Alcántara-Manzanares; Silvia Medina Quintana; Roberto García-Morís; Miguel Jesús López Serrano (Australian Journal of Environmental Education)
This article is an exploratory analysis of the use of humour in Environmental Education, from the perspective of 10 Spanish specialists and educators. Research is carried out using a qualitative methodology through semistructured interviews and a focus group of specialists. The results point to a positive perception of the use of humour and the need for flexibility on the part of the educator to adapt to the particularities of the group and the topics addressed. The differences of opinion lie in the limitations in the use of humour as well as in the recommendations made by the specialists participating in the study, which, given their background, can be considered relevant to the use of humour for environmental education in the Spanish context.